An Analytical Method for Solar Heat Flux in Spacecraft Thermal Management Under Multidimensional Pointing Attitudes - Xing Huang; Tinghao Li; Hua Yi; Yupeng Zhou; Feng Xu; Yatao Ren (Energies)
In order to provide a theoretical basis for the thermal analysis and management of spacecraft/payload interstellar pointing attitudes, which are used for inter-satellite communication, this paper develops an analytical method for solar heat flux under pointing attitudes. The key to solving solar heat flux is calculating the angle between the sun vector and the normal vector of the object surface. Therefore, a method for calculating the included angle is proposed. Firstly, a coordinate system was constructed based on the pointing attitude. Secondly, the angle between the coordinate axis vector and solar vector variation with a true anomaly was calculated. Finally, the reaching direct solar heat flux was obtained using an analytical method or commercial software. Based on the proposed method, the direct solar heat flux of relay satellites in commonly used lunar orbits, including Halo orbits and highly elliptic orbits, was calculated. Thermal analysis on the payload of interstellar laser communication was also conducted in this paper. The calculated temperatures of each mirror ranged from 16.6 °C to 21.2 °C. The highest temperature of the sensor was 20.9 °C, with a 2.3 °C difference from the in-orbit data. The results indicate that the external heat flux analysis method proposed in this article is realistic and reasonable.